Approaches to monitoring changes in carbon stocks for REDD+. Issue 5 (October 2013) - Birdsey, Richard; Angeles-Perez, Gregorio; Kurz, Werner A; Lister, Andrew; Olguin, Marcela; Pan, Yude; Wayson, Craig; Wilson, Barry; Johnson, Kristofer
Reducing emissions from deforestation and forest degradation plus improving forest-management (REDD+) is a mechanism to facilitate tropical countries' participation in climate change mitigation. In this review we focus on the current state of monitoring systems to support implementing REDD+. The main elements of current monitoring systems – Landsat satellites and traditional forest inventories – will continue to be the backbone of many forest-monitoring systems around the world, but new remote-sensing and analytical approaches are addressing monitoring problems specific to the tropics and implementing REDD+. There is increasing recognition of the utility of combining remote sensing with field data using models that integrate information from many sources, which will continue to evolve as new sensors are deployed and as the availability of field data increases.